Compliance of Diabetic Clients: Effect of Nurse-Led Home Care Interventions and Monitoring - Leena, K. C.; Alvares, Irene; Sequeira, Sonia Karen Liz; Pereira, Priya Sweety; Deepika, N. C.; Sequeira, Hazel Asha (Journal of Health and Allied Sciences NU, 2021)
Objectives Type 2 diabetes impacts greatly on quality of life. Health-care providers must focus on efforts to detect, treat, and manage clients through supportive educative approach. This study aims to measure effectiveness of nurse-led home care interventions.Materials and Methods This study among 103 diabetic subjects measured baseline blood pressure (BP), weight, and blood glucose levels. Information on compliance was obtained using a rating scale consisting of domains: dietary habits, exercise, rest, sleep, symptom management, prevention of complications, medication, and follow-up. Individualized comprehensive nursing interventions (education, testing, counselling) were provided, that were reinforced two times a week for 4 weeks, with minimum 7 home visits carried out by the researchers who are registered nurses and teaching faculty along with six interns of BSc nursing program. Post-tests were obtained at second and fourth weeks after start of intervention.Results Significant improvement in blood sugar (p < 0.05), systolic BP (p < 0.001), and diastolic BP (p < 0.001) was observed. There was no change in body mass index (BMI) (p > 0.05). Post-hoc analysis found significant difference between pre-, post1- and post2-measures. Significant association was found between dietary habits and BMI (p < 0.05) and diastolic BP (p < 0.05). Compliance improved from 29 (28.2%) to 47(45.6%), partially compliant from 55 (53.4%) to 45 (43.7%) and noncompliant 19 (18.4%) to 11 (10.7%), with a clear improvement in each of the domains of compliance.Conclusion Individualized comprehensive interventions delivered at the natural environment of families by registered nurses effectively improve compliance to diabetes management.
Keywords: nurse-led interventions; home care nursing; diabetes; visiting nurses; compliance